Implementasi Metode Zig-Zag Chiper Dan ROT13 Untuk Kerahasiaan Basis Data - Deni Anggara; Lili Tanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Databases are widely used to store and manage data and information. despite the fact that database security is very important because data can be stolen from database without any security. The topic in this article contains the Implementation of Zig-Zag Cipher and Rot13 Methods for Database Confidentiality. Research objectives of the article The objectives of this research are as follows; Applying the secrecy of text contents to data in the database, Applying the Zig-Zag Cipher and ROT13 methods for secrecy of database text contents, Generating Applications for Implementation of the Zig-Zag Cipher and ROT13 Methods for Confidentiality of Data in the Database. The research method used is a qualitative method which collects information using books, journals, etc. in the form of literature and applies it to software and hardware. The results of the study using the application of the implementation of the Zig-Zag Cipher and ROT13 methods for database data confidentiality can apply text content secrecy to data in the database. By using the text data from the database and the specified key, then the text data from the database and key are converted to ASCII so that you can then apply the Zig-Zag Cipher and ROT13 methods for the confidentiality of the contents of the database text.